Utility of RAPID score in parapneumonic effusion or empyema: A prospective study at a tertiary centre - Deepak Kumar Suthawal; Govind Singh Rajawat; Suresh Koolwal; Komal Chaudhary (Lung India)
Background: In this study we evaluated the utility of RAPID score in Parapneumonic effusion and empyema. Both of which are most common causes of exudative pleural effusion and this score was developed by Rahman et al by using multicentre intrapleural trial 1[MIST1 and MIST2]. Most of the patients with parapneumonic effusion usually recovers but mortality rate still around 10% along with long hospital stay, surgical interventions requirement, morbidity (3-month follow up) despite of advances in treatment specially in empyema cases. For this reason, this study was done as there is no such study have done by anyone in our knowledge specially in India. After calculating RAPID score in pleural infection then patients were stratified in the different risk categories and association was compared with these risk categories with different variables. Methods: This is a prospective study at tertiary in which clinical utility of RAPID score in pleural infection in INDIAN population where tuberculosis infection is predominant. Baseline RAPID score was calculated on admission and stratified into risk category according to RAPID score. Primary outcome both mortality and morbidity, secondary outcome need of surgical interventions, length of hospital at 3-months in different risk category. Results: Overall, 120 patients were included in this study. Mortality was 7 (5.83%) in our study. Total 17 (14.17%) patients needed surgery and length of hospital study was compared in all three categories of RAPID score. Total 26 (21.67%) patients had <7 days and 94 (78.33%) >7 days hospital stays. Most common organism isolate was mycobacterium tuberculosis. RAPID score was compared in Tubercular And non-tubercular organisms. Conclusion: Prognostic utility of RAPID score is well established especially in non-tubercular organisms. Here, in our study management utility of RAPID score also found useful. It performs good some aspects in tubercular aetiology.